2020
DOI: 10.3390/diagnostics10030176
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Mitochondrial Respiration, Endogenous Coenzyme Q10 and Oxidative Stress in Patients with Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) is characterized by a progressive loss of renal function and a decrease of glomerular filtration rate. Reduced mitochondrial function, coenzyme Q10 (CoQ10), and increased oxidative stress in patients with CKD contribute to the disease progression. We tested whether CoQ10 levels, oxidative stress and platelet mitochondrial bioenergetic function differ between groups of CKD patients. Methods: Twenty-seven CKD patients were enrolled in this trial, 17 patients had arterial hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Low levels of CoQ 10 may be caused by a damage to endogenous CoQ 10 synthesis, or by mutation of one or more of the COQ genes, or by its increased utilization. Signifi cantly lower serum level of CoQ 10 were found in patients with an acute infl uenza infection (15), in patients with chronic kidney disease (38,39), in endomyocardial biopsies of patients after heart transplantation (40) in patients with cardiomyopathy (41), in infertile men (42,43). CoQ 10 has shown the potential to decrease pain and fatigue in patients with fi bromyalgia (44).…”
Section: Is Coenzyme Q 10 the Target Of Sars-cov-2 Virus Causing Co-vmentioning
confidence: 99%
“…Low levels of CoQ 10 may be caused by a damage to endogenous CoQ 10 synthesis, or by mutation of one or more of the COQ genes, or by its increased utilization. Signifi cantly lower serum level of CoQ 10 were found in patients with an acute infl uenza infection (15), in patients with chronic kidney disease (38,39), in endomyocardial biopsies of patients after heart transplantation (40) in patients with cardiomyopathy (41), in infertile men (42,43). CoQ 10 has shown the potential to decrease pain and fatigue in patients with fi bromyalgia (44).…”
Section: Is Coenzyme Q 10 the Target Of Sars-cov-2 Virus Causing Co-vmentioning
confidence: 99%
“…Hence, metabolically highly active but homogenous PLTs might be a valuable surrogate to investigate systemic changes of mitochondrial function, since they are involved in a variety of systemic reactions (e.g., hemostasis, immunoregulation, inflammation or oxidative stress) [18][19][20]. Assessing PLT bioenergetics as a systemic marker has been performed in the context of various diseases [15,19,[21][22][23][24][25][26][27][28] as well as training studies [29][30][31][32][33]. However, changes in PLT bioenergetics after an ultramarathon competition in the context of a field study has not been assessed so far.…”
Section: Introductionmentioning
confidence: 99%
“…Platelets isolated from peripheral blood are an accessible source of mitochondria studied in various diseases, such as lateral amyloid sclerosis [ 10 ], in patients with chronic kidney disease [ 11 , 12 ], in a patient after kidney transplantation [ 13 ], in patients with rheumatoid arthritis [ 14 ], and in aging [ 15 ]. Our previous study showed a reduced platelet mitochondrial metabolism and endogenous CoQ 10 concentration in non-hospitalized patients after 3–6 weeks of acute COVID-19 disease (in platelets, CoQ 10 was reduced vs. control to 70%, p = 0.002) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%